Plasma formation on the front and rear of plastic targets due to high-intensity laser-generated fast electrons - Tatarakis, M; Davies, JR; Lee, P; Norreys, P; Kassapakis, N; Beg, F; Bell, A; Haines, MG; Dangor, A (1998)
Novel features of plasma generation by 1 ps, 1 μm, ∼1019 Wcm-2 laser pulses on thick plastic targets are presented: (i) The electron distribution in the ablated plasma has a minimum along the target normal which persists long after the laser pulse (>1 ns); (ii) a narrow plasma jet is formed at the rear surface after a few picoseconds, in line with the laser focus. This is consistent with a beam of fast electrons traveling through the target, collimated by a magnetic field in the target.